Tower of Sun and Elephant Towers on Treasure Island by Night (H.S. Crocker Co., Inc.)
The Stately Tower of the Sun and the massive Elephant Towers, brilliantly illuminated by night, overlook the Portals of the Pacific at the San Francisco Golden Gate International Exposition.